Evaluation of antioxidant and phytochemical analysis of water extracted root powder of Glycyrrhiza Glabra: Dunumala B.N.V, Paheerathan V., Piratheepkumar R. (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2021)
Glycyrrhiza glabra is a perineal herb containing chemical composition of glabridin and glycyrrhizic acid. Antioxidant substances cause to blocking of the oxidative stress of the human cells and phenolic and flavonoid also have been proved their effectiveness in chronic diseases. In this study, in vitro antioxidant activity, total phenolic and flavonoids content of hot and cold water extract of five different concentrations were determined by using spectrophotometric methods. Total Antioxidant activity of extracts was expressed with frap (ferric reducing antioxidant power) values of tannic acid equivalents/g dry weight. Antioxidant capacity of hot and cold water extract was 129.46±3.4 umol/g and 87.95±4.1 umol/g respectively. Assays of phenolic and flavonoid concentrations were expressed as tannic acid equivalents/g dry weight.Total phenolic content of hot extract was 51.46±8.05 mg /Tannic acid equivalent/g dry material; cold water extract was 37.68±0.50 mg Tannic acid equivalent/g dry material.Total flavonoid content in the hot water extract (144.02±3.52 mg Tannic acid equivalent/g dry material and cold water extract (109.26±1.82mg Tannic acid equivalent/g dry material).Hot water extracts of Glycyrrhiza glabra root powder showed the highest phenolic and flavonoid concentration and strong antioxidant activity. Keywords: Antioxidant, flavonoid, Glycyrrhiza glabra, phenolic, Frap 1Bandaranayake Ayurveda Research Institute, Nawinna, Sri Lanka. 2Unit of Siddha Medicine, Faculty of Applied Science, Trincomalee Campus, Eastern University, Sri Lanka. *Correspondence: Paheerathan V., Senior Lecturer, Unit of Siddha Medicine, Faculty of Applied Science, Trincomalee Campus, Eastern University, Sri Lanka. E mail: geethan1978@live.com